Reduced Expression of Erythropoietin After Intravitreal Ranibizumab in Proliferative Diabetic Retinopathy Patients—Retrospective Interventional Study - Chen, Li; Feng, Jing; Shi, Yanhong; Luan, Fuxiao; Ma, Fang; Wang, Yingjie; Yang, Weiqiang; Tao, Yong (Frontiers in Medicine, 2021)
Purpose: To evaluate the expressions of erythropoietin (EPO) and vascular endothelial growth factor (VEGF) in the vitreous and fibrovascular membranes (FVMs) of proliferative diabetic retinopathy (PDR) after the intravitreal injection of ranibizumab (IVR) and further explore the relationship between EPO and VEGF. Method: The concentrations of EPO and VEGF levels in the vitreous fluid were measured in 35 patients (24 PDR and 11 non-diabetic patients) using enzyme-linked immunosorbent assay. The patients were divided into three groups: PDR with IVR (IVR group) before par plana vitrectomy (n = 10), PDR without IVR (N-IVR group) (n = 14) and a non-diabetic group [macular holes (MHs) or epiretinal membranes (ERM), n = 11]. Fluorescence immunostaining was performed to examine the expressions of VEGF, EPO and CD 105 in the excised epiretinal membranes. Result: The PDR eyes of N-IVR group had the highest vitreous VEGF and EPO levels (836.30 ± 899.50 pg/ml, 99.29 ± 27.77 mIU/ml, respectively) compared to the non-diabetic group (10.98 ± 0.98 pg/ml and 18.96 ± 13.30 mIU/ml /ml). Both the VEGF and EPO levels in the IVR group (13.22 ± 2.72 pg/ml and 68.57 ± 41.47 mIU/ml) were significantly lower than the N-IVR group (p = 0.004 and p = 0.04, respectively). Furthermore, no significant difference was observed for VEGF levels between the non-diabetic and IVR groups (10.9 ± 0.98pg/ml and 13.22 ± 2.72pg/ml, respectively, p = 0.9). Yet the EPO level in the IVR group was significantly higher than that in the non-diabetic group (68.57 ± 41.47pg/ml, and 18.96 ± 13.30pg/ml, respectively, p = 0.001). The expressions of EPO, VEGF and CD105 were significantly reduced in fluorescence immunostaining of FVMs in the IVR group compared with the N-IVR group. The receiver operating characteristic (ROC) curve of the EPO and VEGF levels were 0.951 and 0.938 in the PDR group. Conclusion: Both of the VEGF and EPO level were significantly increased in PDR patients, which have equal diagnostic value in the prediction of PDR. IVR could reduce the EPO level, but not enough to the normal level.